Investigating Students' English Proficiency Based on TOEFL Scores Using the Rasch Model - Ilham Sandy Pratama; Helta Anggia (International Journal of Education, Vocational and Social Science, 2024)
Learning English is very important in the era of globalisation, especially for non-native speakers who want to master English language skills. In the field of education, English as a Foreign Language (EFL) is becoming increasingly important as it is considered an essential skill. Along with the increasing need for English in educational institutions, such as the Test of English as a Foreign Language (TOEFL) is used to measure students' abilities and identify areas that need improvement. This study aims to investigate students' English proficiency using Rasch Model analysis on the TOEFL ITP test. This study used a quantitative approach with data analysed using Winstep 3.73 software. The results showed that students were successful in answering long logical inference questions and short dialogue restatements on listening comprehension, as well as clause questions on written structures & expressions. On reading comprehension, students successfully answered reference questions, vocabulary in context, unstated details, and implied details. This study also found that all subtests on the TOEFL ITP have good reliability and suitability. In conclusion, Rasch Model analysis is effective in identifying the types of TOEFL questions that affect student success, as well as ensuring that the subtests used are reliable and appropriate for the measurement of English language skills.